Stability of mandibular implants with Morse taper and external hexagon connections placed under immediate loading: a longitudinal clinical study - Elara Barelli Paganelli, Oriana; Letícia Santos, Pâmela; Spin-Neto, Rubens; Antonio Pereira Filho, Valfrido [UNESP]; Margonar, Rogério (My University, 2022)
The aim of this study was to compare the longitudinal stability of implants with Morse taper and external hexagon connections placed in the anterior mandible and subjected to immediate functional loading. Nine patients each received 4 mandibular implants placed between the mental foramina. In each patient, 2 implants on the left side of the arch had Morse taper prosthetic connections, and 2 implants on the right side had external hexagon prosthetic connections. Mandibular overdentures and opposing removable complete dentures were placed within 72 hours after implant surgery. Clinical evaluation of the implants via magnetic transduction resonance frequency analysis was performed immediately following surgery and 3 months, 6 months, and 2 years following surgery to obtain the implant stability quotient (ISQ). The data obtained were parametric according to the Kolmogorov-Smirnov normality test. The lowest ISQ of any implant was approximately 67, representing reliable osseointegration. The only statistically significant difference between the 2 types of prosthetic connection was found in the initial period (immediately following surgery), when the external hexagon connection in the distal position presented greater stability than did the Morse taper connection in the same position on the opposite side (P < 0.05; Student t test). In intragroup comparisons, no statistically significant differences were found regarding the positions of the implants in the mandible. When the different follow-up periods were evaluated, there were statistically significant differences only in the external hexagon group, with significant reductions in stability of both mesial and distal implants at 6 months compared to other time periods (P < 0.05; Tukey test). Within the limitations of the study, it can be concluded that both Morse taper and external hexagon prosthetic connections provide good stability in an immediate functional loading protocol.
Keywords: dental implants; dental prosthesis; immediate dental implant loading; osseointegration